Examining a teacher-led physically active mathematics intervention: teachers’ perceptions of the facilitators and barriers to implementation in UK primary schools - Wood, Nathan S.; Cooper, Simon B.; Dring, Karah J.; Magistro, Daniele; Boat, Ruth (Frontiers in Education, 2025)
IntroductionThis study aimed to address a gap in the literature by examining Key Stage One teachers’ perceptions of the facilitators and barriers to implementing physically active mathematics lessons in UK primary schools after administering a physically active mathematics intervention for 6 weeks. Incorporating physical activity into academic lessons presents a unique approach to increasing physical activity among children without compromising the time allotted for academic lessons.MethodsThe intervention was designed in collaboration with the participants and the research team. The study employed a mixed methods approach, utilizing a parallel design in which 14 current key stage one teachers (men = 1, women=13) participated. The participating teachers delivered 6 weeks of physically active mathematics lessons in their respective schools. Training (through two preparatory workshops), schemes of work, and equipment were provided to participants before the intervention began. Survey data were collected through pre- and post-intervention surveys and a weekly intervention delivery log. Participants engaged in individual semi-structured interviews post-intervention. Survey data were analyzed using descriptive statistical analysis.ResultsThe combined average number of minutes participants could implement physically active mathematics lessons each week was 59 min. Paired samples t-tests revealed a significant increase in participants’ confidence in delivering physically active mathematics lessons from pre-intervention (M = 2.86, SD = 2.23) to post-intervention (M = 8.31, SD = 1.07; t (12) = −6.739, p < 0.001). Interview data were transcribed verbatim and analyzed through thematic analysis. Several facilitators and barriers to implementing PALs were identified. Key facilitators identified in this study included training, availability of ready-to-use resources, and increased teacher confidence. Furthermore, physically active lessons (PALs) were easier to implement in contexts where play-based learning approaches from the early years foundations stage could naturally extend into subsequent years. However, key barriers included classroom management challenges, time constraints, and space limitations. Additionally, the specific timing of implementation posed challenges, with cold weather restricting outdoor activities and Christmas-related commitments detracting from the time available for PALs.DiscussionThis study highlights the feasibility of implementing physically active mathematics lessons into the curriculum of UK primary schools and provides key considerations for schools aiming to successfully implement these lessons to best aid the implementation of physically active mathematics lessons.